2018
DOI: 10.3389/fpsyt.2018.00271
|View full text |Cite
|
Sign up to set email alerts
|

IL-33/ST2 Pathway and Galectin-3 as a New Analytes in Pathogenesis and Cardiometabolic Risk Evaluation in Psychosis

Abstract: Schizophrenia and treatment of this disorder are often accompanied with metabolic syndrome and cardiovascular issues. Alterations in the serum level of innate immune mediators, such as interleukin-33 (IL-33) and its receptor IL-33R (ST2) and Galectin-3 (Gal-3) were observed in these conditions. Moreover, these parameters are potential prognostic and therapeutic markers. There is also accumulating evidence that these molecules play a role in neuroinflammation. Therefore, in this study we have investigated the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 67 publications
1
36
0
Order By: Relevance
“…To date, galectin-3 has been examined as a marker for only a few psychiatric disorders including schizophrenia and ADHD. [20][21][22][23] Schizophrenia and galectin-3 levels has been recently investigated. Kajitani et al, 20 noted that the galectin-3 serum levels were increased in chronic schizophrenia and were positively correlated with both the brief psychiatry rating scale (BPRS) positive symptom score and activation score and negatively correlated with the BPRS negative symptom score.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, galectin-3 has been examined as a marker for only a few psychiatric disorders including schizophrenia and ADHD. [20][21][22][23] Schizophrenia and galectin-3 levels has been recently investigated. Kajitani et al, 20 noted that the galectin-3 serum levels were increased in chronic schizophrenia and were positively correlated with both the brief psychiatry rating scale (BPRS) positive symptom score and activation score and negatively correlated with the BPRS negative symptom score.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] One of the two studies examined serum galectin-3 concentrations. 20,21 In one of these studies, Kajitani et al, 20 detected increased serum galectin-3 concentration in patients with schizophrenia. In another study, Borovcanin et al, 21 reported that the concentrations of galectin-3 were elevated in remission and lower in exacerbation of schizophrenia compared to controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Borovcanin et al showed that serum concentrations of gal-3 were significantly lower in first-episode psychosis and schizophrenia in relapse than in healthy controls. 20 They also found higher gal-3 levels in schizophrenia in remission. The authors suggested that gal-3 may mediate the underlying mechanisms of schizophrenia onset, as well as metabolic and cardiovascular changes in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…12 Studies have shown that gal-3 contributes to certain neurological conditions, such as Parkinson disease, 15 prion diseases, 16 and amyotrophic lateral sclerosis. 17 In addition to these studies, gal-3 has also been researched in relation to psychiatric disorders, such as attention deficit hyperactivity disorder, 18 schizophrenia 19,20 and anxiety. 21 To the best of our knowledge, very few studies have evaluated the connection between galectins and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%